Experimental testing of a prototype cantilevered liquid‐nitrogen‐cooled silicon mirror. (5th December 2022) - Cutler, G.; Cocco, D.; Bentley, B.; Cervantes, M.; Chavez, P.; Chrzan, J.; DiMaggio, S.; Hussey, R.; Ilmberger, J.; Lindsay, J.; Lizotte, E.; McCombs, K.; et al.
Abstract : Experimental testing of a liquid‐nitrogen‐cooled silicon mirror is reported. This testing covered fracture, heat transfer, modal response and distortion. Abstract : This report presents testing of a prototype cantilevered liquid‐nitrogen‐cooled silicon mirror. This mirror was designed to be the first mirror for the new soft X‐ray beamlines to be built as part of the Advanced Light Source Upgrade. Test activities focused on fracture, heat transfer, modal response and distortion, and indicated that the mirror functions as intended.